2014
DOI: 10.1128/iai.02130-14
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies against Vibrio vulnificus RtxA1 Elicit Protective Immunity through Distinct Mechanisms

Abstract: g Vibrio vulnificus causes rapidly progressing septicemia with an extremely high mortality rate (>50%), even with aggressive antibiotic treatment. The bacteria secrete multifunctional autoprocessing repeats-in-toxin (MARTX) toxins, which are involved in the pathogenesis of Gram-negative Vibrio species. Recently, we reported that immunization with the C-terminal region of V. vulnificus RtxA1/MARTX Vv , RtxA1-C, elicits a protective immune response against V. vulnificus through a poorly defined mechanism. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 58 publications
(79 reference statements)
0
10
0
Order By: Relevance
“…The identity of this protein was confirmed by western blotting with an anti‐RtxA1‐C monoclonal antibody (22RA) and anti‐serum from V. vulnificus M06‐24/O‐infected mice (Fig. c and data not shown) ; equivalent amounts (100 ng) of purified GST (Fig. c, lane 1) and CPD Vv (C3725S) (Fig.…”
mentioning
confidence: 82%
“…The identity of this protein was confirmed by western blotting with an anti‐RtxA1‐C monoclonal antibody (22RA) and anti‐serum from V. vulnificus M06‐24/O‐infected mice (Fig. c and data not shown) ; equivalent amounts (100 ng) of purified GST (Fig. c, lane 1) and CPD Vv (C3725S) (Fig.…”
mentioning
confidence: 82%
“…Recent studies have shown that protective immunity against Vibrio species is induced by both bacterial components and toxins, including LPS, pili, capsular polysaccharides, cholera toxins and MARTX toxins . Among these protective immunogens, MARTX toxins, which comprise a subfamily of large secreted RTX proteins, have been identified in a number of Vibrio species and other pathogenic gram‐negative bacteria .…”
Section: Cross‐reactivity and Cross‐protectivity Of Anti‐rtxa1‐c‐mabsmentioning
confidence: 99%
“…We previously generated a panel of mAbs against the C‐terminal region (aa residues 3491–4701) of V. vulnificus RtxA1/MARTX Vv , RtxA1‐C . We also characterized the protective activity of anti‐RtxA1‐C mAbs in mouse models of V. vulnificus infection .…”
Section: Cross‐reactivity and Cross‐protectivity Of Anti‐rtxa1‐c‐mabsmentioning
confidence: 99%
See 2 more Smart Citations